Tele-periodontics - Oral health care at a grass root level - Haritha Avula (Wolters Kluwer Medknow Publications, 2015)
A new concept of tele-periodontics, which merges the innovative technology of telecommunications and the field of periodontics, is proposed. This new field of tele-periodontics will have an infinite potential where access to a specialist will be provided at a grass root level, enhancing effective delivery of therapy and information to the rural and under privileged areas. It would allow the specialist and the patient to interact either by video conferencing (real time) or through supportive information (store and forward) over geographic distances. Different probabilities of tele-periodontics such as tele consultation, tele training, tele education and tele support are also discussed in this paper.